2017
DOI: 10.1097/md.0000000000009024
|View full text |Cite
|
Sign up to set email alerts
|

An inflammatory myofibroblastic tumor in the transplanted liver displaying quick wash-in and wash-out on contrast-enhanced ultrasound

Abstract: Rationale:Inflammatory myofibroblastic tumor (IMT) is an uncommon mesenchymal neoplasm, and its presence in a grafted liver is exceedingly rare.Patient concerns:A 54-year-old woman was admitted to our hospital with a half-month history of intermittent melena. She had undergone deceased-donor liver transplantation (LT) for hepatitis B virus related liver cirrhosis without hepatocellular carcinoma 5 months previously.Diagnosis:Laboratory examination showed impaired liver and renal functions and Epstein–Barr viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Infrequent exceptions to this algorithm have been reported for both benign and malignant masses on CEUS; in particular, some well-differentiated HCCs do not show washout [8], likely due to the similar blood volume of the lesion relative to the liver. Some benign liver masses, including hepatic adenomas, focal nodular hyperplasias (FNHs), and inflammatory pseudotumors may show washout [3,25,26]. It should also be noted that in patients with advanced cirrhosis, the presence and degree of washout of a focal liver lesion may be affected by poor enhancement of the background parenchyma due to decreased portal venous perfusion [27] and decreased vascular volume in the cirrhotic liver.…”
Section: Significance Of Washout In Differentiating Focal Liver Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrequent exceptions to this algorithm have been reported for both benign and malignant masses on CEUS; in particular, some well-differentiated HCCs do not show washout [8], likely due to the similar blood volume of the lesion relative to the liver. Some benign liver masses, including hepatic adenomas, focal nodular hyperplasias (FNHs), and inflammatory pseudotumors may show washout [3,25,26]. It should also be noted that in patients with advanced cirrhosis, the presence and degree of washout of a focal liver lesion may be affected by poor enhancement of the background parenchyma due to decreased portal venous perfusion [27] and decreased vascular volume in the cirrhotic liver.…”
Section: Significance Of Washout In Differentiating Focal Liver Lesionsmentioning
confidence: 99%
“…In the arterial phase, real-time assessment may demonstrate the characteristic spoke-wheel pattern of APHE with an inside-to-outside, or centrifugal, filling pattern [4] in typical cases of FNH. Studies have shown that some hepatocellular adenomas [25] and inflammatory pseudotumors [3,26] demonstrate washout. Adenomas often show APHE and demonstrate either sustained enhancement or mild washout in the late phase [25,53].…”
Section: Benign Entities Showing Washout: Potential Pitfallsmentioning
confidence: 99%